1994
DOI: 10.1177/026835559400900406
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Skin Microcirculation in Patients with Chronic Venous Insufficiency Assessed by Laser Doppler Fluxmetry and Transcutaneous Oxymetry

Abstract: Objective: To evaluate whether microcirculatory disturbances of the skin in patients with chronic venous insufficiency are a generalized phenomenon or restricted to visible skin changes. Design: Open, prospective study in patients and healthy, age-matched subjects. Setting: Department of Angiology, Hannover Medical School. Patients: Seventy-one patients with chronic venous insufficiency. Measurements: Transcutaneous oxygen pressure (tc Po2) at electrode core temperatures of 37°C and 44°C and laser Doppler flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…Measurements show an increased median basal resting flux in patients with CVI and AB lesions compared with normal skin. 90–93 Venous hypertension results in a similar decrease of flux in AB lesions or normal skin (46% in normal, 56% in AB lesions). 93 …”
Section: Microcirculationmentioning
confidence: 95%
“…Measurements show an increased median basal resting flux in patients with CVI and AB lesions compared with normal skin. 90–93 Venous hypertension results in a similar decrease of flux in AB lesions or normal skin (46% in normal, 56% in AB lesions). 93 …”
Section: Microcirculationmentioning
confidence: 95%
“…They found that a single IPC treatment diminished the laser Doppler £ux and enhanced the venoarteriolar response of the skin in legs with CVI. Other investigators (8,10,14), have, however, found the venoarteriolar response to be una¡ected in legs with CVI compared with healthy legs. Pryce & Friedmann (9) found the venoarteriolar response to be increased in legs with CVI compared with healthy legs.…”
Section: Discussionmentioning
confidence: 91%
“…The arterial resistance is lowered at angiography (16^18) and the oxygen content of venous blood is elevated in legs with CVI (16,19). Accordingly, the transcutaneous oxygen tension (TcPO 2 ) is lowered (5^7, 13,14) and oxygen extraction is reduced (15) in the skin of legs with CVI. All these ¢ndings can re£ect enhanced whole skin blood £ow while there is ischaemia in the nutritional capillary bed (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic venous insufficiency (CVI) has been shown to be associated with biochemical abnormalities in the vein wall and functional abnormalities ranging from haemorheological changes [1][2][3][4], increased capillary permeabili ty, trapping of white blood cells [5][6][7], deficiencies of pro teins involved in coagulation and fibrinolytic systems [8] to microcirculatory changes [9][10][11][12]. These disorders are aggravated by venous hypertension produced by standing or sitting as well as by venous occlusion [1,2, 13, 14] and may lead to trophic skin changes and ulceration.…”
Section: Introductionmentioning
confidence: 99%